Blended Learning with the Flipped Classroom Method: A Post-Pandemic Solution and Future Trend - Zulaikhah, Siti; Hasanah, Ida Faridatul; Sutiyono, Agus; Rohmat, Rohmat; Wibowo, Gita Vallenti (Universitas Islam Negeri Raden Intan Lampung, 2024)
Technological advancements have significantly impacted various aspects of life, particularly education. The Covid-19 pandemic, which lasted for over two years, further disrupted the education sector, necessitating a shift in teaching and learning practices. New policies, often referred to as the